Tingkat Kesehatan TINGKAT KESEHATAN PERUSAHAAN INFRASTRUKTUR SEBELUM DAN SELAMA PANDEMI COVID-19 BERDASARKAN SURAT KEPUTUSAN MENTERI BUMN NOMOR: KEP-100/MBU/2002: TINGKAT KESEHATAN PERUSAHAAN INFRASTRUKTUR SEBELUM DAN SELAMA PANDEMI COVID-19 BERDASARKAN SURAT KEPUTUSAN MENTERI BUMN NOMOR: KEP-100/MBU/2002 - Deswita, Fadila Putri; Destalia, Mediya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the difference in the health level of state-owned companies in the infrastructure sector listed on the IDX in 2018-2021 before and during the Covid-19 pandemic using ratios on financial aspects in the Decree of the Minister of SOEs Number: KEP-100 / MBU / 2002, namely Return On Equity (ROE), Return On Investment (ROI), Cash Ratio, Current Ratio, Collection Periods (CP), Inventory Turnover (ITO), Total Asset Turnover (TATO), and Total Own Capital to Total Assets (TMS to TA). This research uses quantitative methods and comparative research. Purposive sampling was used to select the sample of this study which amounted to 8 companies. Data collection is obtained in the form of documentation of the company's financial statements on the IDX website. Quantitative data analysis, descriptive statistics, data normality tests, and Multivariate Discriminant Analysis (MDA) hypothesis testing with SPSS version 26 were used in this study. The results showed a significant difference in the health level of state-owned companies in the infrastructure sector between before and during the Covid-19 pandemic. Then TATO, ITO, and TMS against TA are variables that distinguish the level of company health, with TATO as the most dominant variable.